Stability of DIII-D high-performance, negative central shear discharges. (20th March 2017) - Hanson, J.M.; Berkery, J.W.; Bialek, J.; Clement, M.; Ferron, J.R.; Garofalo, A.M.; Holcomb, C.T.; La Haye, R.J.; Lanctot, M.J.; Luce, T.C.; Navratil, G.A.; Olofsson, K.E.J.; et al.
Abstract: Tokamak plasma experiments on the DIII-D device (Luxon et al 2005 Fusion Sci. Tech .48 807) demonstrate high-performance, negative central shear (NCS) equilibria with enhanced stability when the minimum safety factor q m i n exceeds 2, qualitatively confirming theoretical predictions of favorable stability in the NCS regime. The discharges exhibit good confinement with an L-mode enhancement factor H 89   =  2.5, and are ultimately limited by the ideal-wall external kink stability boundary as predicted by ideal MHD theory, as long as tearing mode (TM) locking events, resistive wall modes (RWMs), and internal kink modes are properly avoided or controlled. Although the discharges exhibit rotating TMs, locking events are avoided as long as a threshold minimum safety factor value q m i n > 2 is maintained. Fast timescale magnetic feedback control ameliorates RWM activity, expanding the stable operating space and allowing access to β N values approaching the ideal-wall limit. Quickly growing and rotating instabilities consistent with internal kink mode dynamics are encountered when the ideal-wall limit is reached. The RWM events largely occur between the no- and ideal-wall pressure limits predicted by ideal MHD. However, evaluating kinetic contributions to the RWM dispersion relation results in a prediction of passive stability in this regime due to high plasma rotation. In addition, the ideal MHD stability analysis predicts that the ideal-wall limit can be further increased to β N > 4 by broadening the current profile. This path toward improved stability has the potential advantage of being compatible with the bootstrap-dominated equilibria envisioned for advanced tokamak (AT) fusion reactors.